Comprehensive Investigations of Injection Molding and Additive Manufacturing on Mechanical and Structural Characteristics of Polylactide Composites Loaded With Basalt Fiber Involving Bio-Based Compatibilizers - Arslan, Çağrıalp; Tayfun, Ümit; Yılmaz, Volkan Murat; Delikanlı, Niyazi Erdem; Yılmaz, Volkan Murat; Tayfun, Ümit; Delikanlı, Niyazi Erdem; Arslan, Çağrıalp (Wiley, 2026)
Material researchers studying the shaping of pure polymers and polymer composites in recent years have directed their attention to new techniques and methods. In this context, there is an attention-getter increase in the production of polymeric composite materials via 3D printing (3DP), also known as additive manufacturing (AM). Polylactide (PLA), both as a matrix material and a pure polymer, is among the most preferred materials for this process. The study aims to develop PLA-based biocomposites reinforced with chopped basalt fiber (BF) containing eco-compatibilizers for use in 3D printers as a feedstock and to produce biodegradable composite parts from these composite pellets. The final characteristics of the melt-compounded PLA/BF composites were compared and optimized with those of the produced composites using a conventional method (injection molding (IM)). Considering the study outputs, the styrene-b-farnesene copolymer bio-compatibilizers used in 10 and 15 wt% ratios significantly enhance the mechanical performance of the eco-composites produced by both IM and 3DP. In composites containing Bio-compatibilizer-2, improvements are observed in the tensile and flexural performance of composites produced via the IM process. However, 3DP samples have certain handicaps due to their material structure, which causes them to display relatively lower performance than those produced by the IM. The PLA/BF eco-composite, which is processed by 3DP containing 15 wt% Bio-compatibilizer-2, exhibits the highest mechanical performance. Findings indicate that additive manufacturing is a competitive production technique over traditional injection molding to achieve the required mechanical and structural behavior of BF-reinforced PLA-based composites.
Keywords: Additive Manufacturing; Basalt Fiber; Bio-Composites; Logistics; Polylactide; Polymer Processing